Analisis Kesulitan Memahami Konsep Matematis Ditinjau dari Kemampuan Metakognisi Siswa Pada Siswa Kelas X SMA Negeri 1 Sibolga - Lubis, Mara Samin (Program Studi Pendidikan Matematika FKIP UNIVA Medan, 2024)
This research aims to understand how difficulties in understanding mathematical concepts are related to the metacognitive abilities of class X students at SMA Negeri 1 Sibolga for the 2023/2024 academic year. The research method used in this study is descriptive qualitative. The research subjects consisted of 32 students of class X MIA 2. Data collection was carried out through the use of questionnaires and tests as research instruments. The results of the research show that students with very high metacognitive abilities are able to fulfill all indicators completely, such as restating the concepts studied, classifying objects based on the requirements that form the concept, identifying the properties of operations or concepts, applying concepts logically, providing examples or are not examples of concepts that have been studied, and present concepts in various forms of mathematical representation. Students with high metacognitive abilities are only able to fulfill five of the six existing indicators. Meanwhile, students with moderate metacognitive abilities can only fulfill one indicator, namely providing examples or non-examples of the concepts they have studied